Scorpionism in Pará, Brazil: Clinical assessment of neuromuscular manifestations - Rosicléia Freitas Borges; Joyce Nascimento Dergan; Pasesa Pascuala Quispe Torrez; Vera Lúcia Teixeira de Freitas; Maria Rita Bertolozzi; Átila Barros Magalhães; Fernanda Jacqueline Teixeira Cardoso; Rogério Bertani; Francisco Oscar de Siqueira França (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Background: In the western region of Pará (Brazil), the clinical manifestations of scorpionism exhibit unique characteristics, and there is currently no proposal for a quantitative assessment of this condition. This manuscript proposes and applies a classification system for assessing the severity of scorpionism, comparing it with the system used by the Ministry of Health. Methods: This quantitative, descriptive, observational, cross-sectional study evaluated victims of scorpionism treated at the Municipal Hospital of Rurópolis in Pará, Brazil. Clinical and therapeutic data were collected using instruments and scales, particularly the International Cooperative Scale for the Evaluation of Ataxias. Results: Thirty-four patients were assessed between January and July 2023. The majority were young males. All presented with pain, an 'electric shock sensation' and myoclonus. Muscle spasms were observed in 65% of patients, postural changes in 64%, dysmetria in 55%, altered eye movements in 50%, and dysarthria in 44%. While these manifestations are transitory, they cause significant discomfort to the patient. The classification proposed in this study was compared to the Ministry of Health's Severity Classification, and low agreement between the two classifications was shown (only in 50% of cases). The proposed classification raised the severity of 17 patients by one degree: fifteen from mild to moderate and two from moderate to severe, one of whom developed rhabdomyolysis and acute kidney injury. Conclusions: The proposed classification was beneficial and could be used in the future to assess the effectiveness of therapeutic interventions for this frequent and neglected condition in the Amazon.